Synthesis, Photophysical Properties and DNA-Binding Studies of p-Hydroxy and m-Hydroxy Amphiphilic Porphyrins - Zhang, Jie; Jin, Haiwei; Gao, Dongchun; Jia, Wenping; Li, Fang; Zhang, Ping; Song, Tongtong; Wang, Jiali (Asian Journal of Chemistry, 2014)
Three p-hydroxy and m-hydroxy amphiphilic porphyrins had been synthesized and fully characterized by 1H NMR, IR and FAB-MS. Their photophysical properties were also determined. Furthermore, the UV-visible absorption and fluorescence emission titration experiments indicate that porphyrins and DNA existed an outside binding mode. In addition, the DNA binding constant of 4pOH-TPP, 3pOH-TPP and 4mOH-TPP were determined.